The immunology of cardiovascular homeostasis and pathology - Sattler, Susanne; Kennedy-Lydon, Teresa (Advances in experimental medicine and biology ;, 2017)
"Cardiovascular immunology is a newly emerging research area, investigating the crosstalk between the cardiovascular and the immune system. This crosstalk is evident through (1) crucial immunological capacities and functions of cardiovascular cell types, including cardiomyocytes, fibroblasts, endothelial cells, pericytes and cardiac resident macrophages, (2) the impact of aberrant immune function on the development of cardiovascular disease such as atherosclerosis, direct and indirect immune-mediated heart disease and vasculitis, and (3) the crucial role of the immune system in cardiac repair and regeneration. The Immunology of Cardiovascular Homeostasis and Pathology covers all these aspects of cardiovascular immunology, starting with homeostatic immunological functions of traditional cardiovascular cell types, and moving then to the role of the immune system in cardiovascular pathology and to recent research into targeting the immune system to boost cardiac healing and regeneration"--Publisher's description.